Dynamic source routing protocol with transmission control and user datagram protocols - Saed Thuneibat; Buthayna Al Sharaa (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Dynamic source routing protocol (DSR) is a common routing protocol in wireless network without infrastructure, called ad-hoc network, DSR used just above internet protocol (IP) at the network layer. The upper transport layer provides reliability by transmission control protocol (TCP) and user datagram protocol (UDP). The choice between DSR/TCP and DSR/UDP is an actual issue for network designers and engineers. The question arises: which one provides better quality of service (QoS) parameters, less delay and jitter, greater throughput, and data rates. This paper focuses on the study and analysis of DSR and comparison of DSR/TCP and DSR/UDP by simulation in network simulator (NS2) environment. Another comparison of DSR and ad hoc on-demand distance vector (AODV) is provided. Design and simulation of the protocols in ad hoc network accurately describe the behavior in real system and QoS parameters are obtained.